The Relationship between Homocysteine Levels, MTHFR C677T and A1298C Polymorphism, and Pregnancy Outcomes in Georgian Women with Polycystic Ovary Syndrome: A Case-Control Study - Elene Asanidze; Zurab R. Tsetskhladze; Jenaro Kristesashvili; Marina Pirtskhalava; Manana Urjumelashvili; Shorena Tchiokadze; Malkhaz Vakhania; Nino Parunashvili; Aleksandre Asanidze (International Journal of Fertility and Sterility)
Background: Over the past decade, numerous studies have been conducted to determine the role of homocysteineand methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in the pathogenesis of polycystic ovary syndrome(PCOS), yet the results are inconsistent. The aim of the current study was to determine the association betweenhomocysteine levels (Hcy), MTHFR C677T and A1298C polymorphisms, and pregnancy outcomes in Georgianwomen with PCOS.Materials and Methods: This case-control study included 177 female participants, of which 96 women werediagnosed with PCOS, and 81 age-matched women were without PCOS. Participants were divided into fourgroups; group I: 59 PCOS patients with history of recurrent pregnancy loss (RPL), group II: 37 PCOS patientswith live birth in history and without RPL, group III: 39 women with RPL, without PCOS, group IV: controls,42 women with live birth in history, without RPL and PCOS. These groups were compared based on their serumHcy and the presence of two common single nucleotide polymorphisms (SNPs) in the MTHFR gene: C677T andA1298C.Results: The mean Hcy, frequency of hyperhomocysteinemia (Hhcy) and the prevalence of C677T and A1298Cpolymorphisms in MTHFR gene in PCOS patients were significantly higher than those without PCOS (P<0.05).Group I (PCOS with RPL) showed significantly elevated Hcy (13.7 ± 2.7) compared to group II (10.3 ± 2.6),group III (11.5 ± 2.3), and group IV (7.3 ± 2.2), P<0.001. In group I, the frequencies of the C677T-CT, A1298CACgenotypes, and the compound heterozygous of C677T-CT/A1298C-AC were significantly higher than in theother groups (P<0.05). The prevalence of MTHFR A1298C (CC) was significantly higher in group II (PCOSpatients with live birth) than in other comparison groups (P<0.05).Conclusion: The study reveals a significant correlation between hyperhomocysteinemia, MTHFR polymorphisms(C677T and A1298C), and PCOS, impacting pregnancy outcomes.